Non-invasive detection of Orthohalarachne attenuata (Banks, 1910) and Orthohalarachne diminuata (Doetschman, 1944) (Acari: Halarachnidae) in free-ranging synanthropic South American sea lions Otaria flavescens (Shaw, 1800) - Helena Rivera-Luna; Edwin Kniha; Pamela Muñoz; Javier Painean; Folko Balfanz; Stephan Hering-Hagenbeck; Heinrich Prosl; Julia Walochnik; Anja Taubert; Carlos Hermosilla; David Ebmer (International Journal for Parasitology: Parasites and Wildlife, 2023)
Respiratory mites of the genera Orthohalarachne and Halarachne (Acari: Halarachnidae) are causative agents of nasopharyngeal/nasopulmonary acariasis in pinnipeds and sea otters. Until now, these endoparasitic mites were mainly diagnosed via necropsies and invasive procedures. So far, non-invasive diagnostic techniques have neither been developed nor applied in free-ranging pinnipeds. In the current study, we aimed to evaluate the halarachnid mite infestation status of free-ranging “urban” South American sea lions Otaria flavescens in the city of Valdivia, Chile. Therefore, non-invasive sampling methods were used in the current study, e. g. by observation-based sampling of freshly expectorated nasal mucus in the animal environment. Further, collection devices were developed for target-oriented sampling of sneezed nasal mucus, including sterile petri dishes and stretched clingfilms mounted on telescopic rods. Applying these techniques, 26 individual sputum samples were collected. 11.5% of sputum samples proved positive for halarachnid larvae (in total, n = 7), which were morphologically identified as Orthohalarachne attenuata (n = 2) or Orthohalarachne diminuata (n = 5). In one of the individual sea lion mucus samples, both Orthohalarachne species were detected, thereby confirming a patent co-infestation in vivo. 16S rDNA-based molecular identification of individual Orthohalarachne spp. larvae confirmed morphological findings. For the first time, we here molecularly characterized Orthohalarachne spp. on the basis of three gene regions [18S, 28S and the internal transcribed spacer 1 (ITS1)]. Overall, current data include the successful application of non-invasive techniques to sample halarachnid mites from free-ranging synanthropic pinnipeds and contribute to the current knowledge on respiratory mites infesting South American sea lions by combining morphological and molecular methods to overcome challenges in species identification. This study should further serve as baseline study and calls for more research on occurrence, biology and health implications of orthohalarachnosis in free-living as well as captive pinnipeds.